Politics and opinion in crisis 1678 - 81 - Knights, Mark (Cambridge studies in early modern British history, 1994)
Part II explores public opinion in the country as a whole, and argues that propaganda, electioneering, religious conflict and petitions and addresses committed men to organised networks of belief, but also ensured a struggle about the representation of the will of the people